AGE OF UPPER PALEOZOIC DEPOSITS IN EASTERN MARGIN OF THE TUNGUSKA SYNECLISE: IMPLICATIONS FROM PALYNOLOGICAL DATA - Oshurkova M.V. (My University, 1999)
Spore-and-pollen analysis of the Lapcha and Botuoba formations revealed four successive palynological assemblages. On the basis of the relative abundance of taxa and of the taxonomic composition of the assemblages, the Lapcha and Botuoba formations are attributed to the Upper Carboniferous and Lower Permian, respectively. The revealed palynofloras are correlated with the Upper Carboniferous and Lower Permian palynological zonation in the Kuznetsk coal basin.
Keywords: Paleozoic; Paleozoic; Палеозой